The Impact of Cooperative Learning on University Students’ Academic Goals - Mendo-Lázaro, Santiago; León-del-Barco, Benito; Polo-del-Río, María-Isabel; López-Ramos, Víctor M. (Frontiers in Psychology, 2022)
Cooperative learning encourages the development of interpersonal skills and motivates students to participate more actively in the teaching and learning process. This study explores the impact of cooperative learning on the academic goals influencing university students’ behavior and leading to the attainment of a series of academic objectives. To this end, a quasi-experimental pretest-posttest control group design was used, with a sample of 509 university students from Preschool, Primary and Social Education undergraduate degree courses. Using the Academic Goals Questionnaire (AGQ), pretest and posttest measures were taken via self-reports to evaluate three types of academic goals: learning goals, social reinforcement goals and achievement goals. The results show that cooperative learning is an effective tool for encouraging university students to develop academic goals that motivate them to fully engage with the tasks they are set in order to acquire knowledge and skills (learning goals). In addition, when students are asked to work as part of a team on an autonomous basis without the structure and supervision necessary to ensure a minimum standard of cooperation, they display a greater tendency toward social reinforcement goals than toward learning and achievement goals. These findings contribute new knowledge to the conceptual framework on cooperative learning. Goals may be considered one of the most important variables influencing students’ learning and the use of cooperative learning techniques in university classrooms creates the necessary conditions for encouraging students to develop goals oriented toward learning.